2018
DOI: 10.1007/s12039-018-1468-6
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal catalyzed C-H activation for the synthesis of medicinally relevant molecules: A Review

Abstract: bond formation tool box. This represents such an alternative which has provided the greener solutions to the organometallic/synthetic organic chemistry aiming to the synthesis of complex molecules. In recent years, there has been explosive growth in this area. In this review article we have presented effective methods of C-H activation employed in the synthesis of medicinally relevant molecules since 2010.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…CH bond activation [ 1–5 ] has attracted extensive attention in organic syntheses. [ 6–11 ] Particularly, palladium‐catalyzed direct arylation involves coupling of the aryl halide with the sp 2 ‐sp 2 CH functionality to accomplish aryl–aryl bond formation.…”
Section: Methodsmentioning
confidence: 99%
“…CH bond activation [ 1–5 ] has attracted extensive attention in organic syntheses. [ 6–11 ] Particularly, palladium‐catalyzed direct arylation involves coupling of the aryl halide with the sp 2 ‐sp 2 CH functionality to accomplish aryl–aryl bond formation.…”
Section: Methodsmentioning
confidence: 99%
“…Surprisingly, no detailed studies of this phenomenon have been reported that makes following each piece of this puzzle in the literature very difficult. This is even more remarkable as in the area of CH functionalization (Scheme 26), many CH‐activation processes at aliphatic C(sp 3 )‐ or C(sp 2 )‐carbons with C–C or C–X bond formation have been described recently …”
Section: Aliphatic C(sp3)‐h Hydrogen Isotope Exchange Reactionsmentioning
confidence: 95%
“…Transition-metal-catalysed direct functionalization of C–H bonds is emerging as one of the most important tools for carbon–carbon bond formation [ 107 , 108 , 109 , 110 , 111 , 112 ]. In particular, direct alkenylation of an inert vinylic C−H bond is particularly attractive for constructing the 1,3-diene moiety, as alkenes are naturally abundant an readily available [ 113 ].…”
Section: Transition Metal-catalysed Cross-coupling Reactionsmentioning
confidence: 99%